Assessing the impact of timely diagnosis on psychological outcomes and quality of life for cancer patients: A scoping review - Laura Boswell; Jenny Harris; Richard Green; Jo Armes; Georgia B. Black; Katriina L. Whitaker (PLoS ONE, 2026)
Objective We explored the literature on timely cancer diagnosis and its significance on psychological outcomes or quality of life in cancer patients. Design A scoping review to map existing literature in this area, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews. Results Six studies were identified. Four studies used cross-sectional surveys, and one each used qualitative and mixed-method designs. Quantitative evidence suggests that timely diagnosis was associated with better psychological outcomes and quality of life. Qualitative and mixed-method evidence found an incidental relationship, but it was not a focus of the studies. There were varied definitions of timely diagnosis, and a diverse range of measures were used to identify outcomes. No study satisfied all quality appraisal criteria, with key dates in the diagnostic journey being the least reported (0/6 studies). Conclusions Preliminary evidence indicates that timely diagnosis may be associated with variations in psychological outcomes and quality of life in patients with cancer; however, methodological heterogeneity restricts the generalisability of the findings. More high-quality longitudinal quantitative and qualitative research is needed to explore the direction of the association and lived experience during the adjustment process.